(untitled) (Politeja, 2019)
In 2010, Polish far-right nationalist groups hit upon the idea of establishing one common nationwide march to celebrate National Independence Day in Poland. Since then, the participants have manifested their attachment to Polish tradition, and their anti-multicultural attitude. Much of the debate about multiculturalism and the emergence of conflictual and socially divisive ethnic groupings has addressed ethical concerns. In contrast, this paper focuses on the semiotic and structural level of the problem.